Lumbar Sympathicolysis in Patients with Severe Peripheral Artery Disease: Hemodynamics of the Lower Limbs Determined by Near-Infrared Spectroscopy, Color Coded Duplex Sonography, and Temperature Measurement. Issue 8 (January 2014) - Bombor, Ingmar; Wissgott, Christian; Andresen, Reimer
The objective was to investigate the effects of CT-guided lumbar sympathicolysis on somatic regional oxygen saturation, arterial flow velocity, and skin temperature of the lower limbs in patients with advanced peripheral artery disease (PAD). CT-guided lumbar sympathicolysis was additionally performed after successful revascularization therapy in 61 patients with PAD in categories 5 and 6 according to Rutherford. Somatic regional oxygen saturation in the distal lower limbs was determined semiquantitatively with a near-infrared spectroscopy (NIRS) system. Before and after intervention, peak flow and end-diastolic flow velocity in the dorsalis pedis artery were determined by means of color-coded duplex sonography, and the skin temperature of the feet was measured with an infrared thermometer. After CT-guided lumbar sympathicolysis, somatic regional oxygen saturation, peak flow, end-diastolic flow velocity, and skin temperature in the lower limbs increased significantly.